Masculinidades e facções criminosas nas evidências discursivas acerca do adolescente em conflito com a lei na unidade de internação masculina São Luís - COSTA, Amanda Cristina De Aquino (2019)
This paper aims to analyze discursive evidences which were made by the Justice System and by teenagers who were in a socioeducational measure in an enclosed environment, about the interaction between teenagers and groups known as “criminal groups” (facções criminais) and their relation to the types of social construction of the male gender. In order to achieve the general objective, we will make juridical discussions on the types of social control and socioeducational justice system, based on the theoretical contribution of the Critical Criminology, which conceives criminality as a reality which is formed by processes of social interaction, with logically linked mechanisms, which are selectively applied to the disadvantage of vulnerable groups and on mechanisms of life and death management within the modern State. Then, the guiding principles of the socioeducational system and the legal definitions of infraction and socioeducational measure are discussed as parameters for a critical reflection about social reaction to the infraction act. Next, we enter into the adolescence, youth, and masculinity concepts to discuss how these factors interrelate with the management and propagation of violent practices. Here, we also search for the problematization concerning the role that class and race play as differential markers in the masculinity production. Next, the concept of organized crime and the points in which it gets closer or further from what is known as criminal groups are discussed, and we explain the emergence of groups such as Bonde dos 40, Primeiro Comando da Capital (PCC), and Comando Vermelho (CV). Next, some methodological considerations are presented regarding the type of research, the applied quanti-qualitative approach, the particularity of criminology research, and the clarification of the field which was elected for the gathering of data and subjects of the research. Finally, we present the results of the field research which was carried out in the Unidade de Internação Masculina São Luís, of the Fundação da Criança e do Adolescente (FUNAC), where the document analysis of judicial decisions and of management reports on the adolescents, and the semi-structured interview application with the inmates were held. Based on the collected results, we discussed the social reaction to the committed infractions, and we problematized the categories “masculinities” and “criminal groups” in the discourse of the Socioeducational Justice System and in the own words of the adolescents.